2011
DOI: 10.3314/jjmm.52.145
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Cinnamaldehyde and Potentiation of its Efficacy in Combination with Methylcellulose on Murine Oral Candidiasis

Abstract: We examined the therapeutic effects of cinnamaldehyde and the potentiation of those effects with cassia and cinnamaldehyde when combined with the food additive methylcellulose against murine oral candidiasis. When 19.5 mg/ml of cinnamaldehyde was administered in the oral cavity of Candida infected mice, the oral symptoms were improved. Furthermore, when either a cassia or a cinnamaldehyde preparation in combination with methylcellulose was administered to oral candidiasis-inflicted mice, the therapeutic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In this study, we demonstrated that pretreatment of C. albicans with cinnamaldehyde(2, 000 µg/ml) for just 1 minute, exerted an inhibitory activity on its hyphal growth. The dose of 2, 000 µg/ml seems somewhat higher than that usually intaken in daily life, but this concentration has been reported as safe to be consumed 9,10,24) .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, we demonstrated that pretreatment of C. albicans with cinnamaldehyde(2, 000 µg/ml) for just 1 minute, exerted an inhibitory activity on its hyphal growth. The dose of 2, 000 µg/ml seems somewhat higher than that usually intaken in daily life, but this concentration has been reported as safe to be consumed 9,10,24) .…”
Section: Discussionmentioning
confidence: 87%
“…After the microscopic observation of Candida growth, the medium was aspirated, and then 200µl of the cinnamaldehyde preparation was loaded onto the microplate and incubated at 37, 40, 42.5, and 45ºC for 1, 20, 40, and 60 minutes. The conditions of pretreatment time and temperature were established on the assumption that cinnamaldehyde is used in gargles and foods such as candy, chewing gum, and spiced tea 10,14) . (Since it is reported that humans perceive heat stimuli(>= 46ºC)as unpleasant contact, temperature conditions were set at less than 45ºC 15−17) .…”
Section: Preparation Of Cinnamaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…This potential could be realized by optimizing delivery and dosage. Increasing the viscosity of the delivery vehicle might increase the time the peptide is in contact with the cells causing the candidiasis, as in the case of therapeutic activity of cinnamaldehyde (Taguchi et al ., ). We believe that such improvements could lead to effective therapies for immunocompromised patients at greatest risk of azole‐resistant Candida infections and thus expand the applicability of the inexpensive and well‐tolerated azole drugs.…”
Section: Discussionmentioning
confidence: 97%
“…The mice were infected orally by rolling a cotton swab (baby cotton buds; Johnson & Johnson Co., Tokyo, Japan) soaked in a suspension of C. albicans cells (2–3 × 10 8 viable cells mL −1 in RPMI 1640 medium containing 2.5% fetal calf serum) over all areas of the mouth. The number of Candida cells inoculated in the oral cavity was calculated to be about 1~1.5 × 10 6 cells per mouse based on the difference in viable cell number present on the cotton swabs before and after oral inoculation (Taguchi et al ., ).…”
Section: Methodsmentioning
confidence: 97%